Analisis Presepsi Penggunaan Aplikasi BRImo Dengan Pendekatan Technology Acceptance Model (TAM) Mahasiswa Universitas Merdeka Malang - Azhari, Ivan Dwi Nur (Computing Insight : Journal of Computer Science, 2025)
Bank Rakyat Indonesia (BRI) is one of the largest government-owned banks in Indonesia. In the development Â of digital era like this, online services become the choice of most of the clients. This is due to ease of doing any kind of banking transaction. Along with the inclusion of smartphones as a device that is needed by most people today, the Bank BRI provides Mobile Banking facilities named "BRImo" which stands for BRI Mobile. Based on the short ratings and reviews on Google Playstore Many BRImo users have encountered problems such as the difficulties of using BRImo, and sometimes users are often blocked themselves on the BRImo app. Therefore, BRImo is required to add value to the applications it uses and understand how consumers conduct and perception of the services they develop. By knowing the factors affecting user acceptance of the provided online banking application, it would be a recommendation for BRImo to improve its effectiveness and service, thereby becoming a competitive advantage for Company. There are many models developed by researchers to measure the acceptance of information systems by users, one of which is Technology Acceptance Model (TAM) and found that variables Perceived Usefulness, Perceived Ease Of Use, and Actual Use has no effect on interests using the BRImo app, while the Perceived Enjoyment variable affects interests using the BRImo app. Keywords: Actual Use, BRImo application, Technology Acceptance Model (TAM)